Rancang Bangun Sistem Pengolahan Surat Masuk Dan Surat Keluar Menggunakan Teknik Sequential Search Di Kantor Pusat Kspps Bmt Csi Syariah Sejahtera - Wahyono Nur Fitri (INFOKOM, 2018)
One of the communication tools is written in the Office is a letter. Over time, the number of letters that exist in a company more and more, so that arise problems in managing them either when the recording process as well as the disposition of letter, as well as disbursements archive Epistle. At the headquarters of KSPPS BMT CSI Syariah Sejahtera, letters there are stored in files that are still manual, so as to allow the first letter, and take a long time in the liquefaction and processing. By making use of computer technology, the author tried to design and build a mail and archiving management systems to cope with the above problems. The methods used are observation, interview, librarianship, analysis, design, development systems, test systems, and implementation. The making of this application was built for the management of incoming mail, and mail out. Results of the research is to use the Mail Data Processing Applications extremely assist employees in a letter and then enter the data store to database so scattered or loss of letters can be avoided.